Malignant granular cell tumor in the thoracic wall: A case report - Gao, Shengnan; Xing, Bin; Lichao, Sun; Luo, Jie; Tang, Jiao; Wang, Ye; Zhang, Xiaoyan (Frontiers in Oncology, 2022)
Abstract Granulosa cell tumor (GCT) is a rare tumor that originated from neural / Schwann cells. It can occur at any age and any site of the body. The most common is the tongue, followed by the mammary gland, upper respiratory tract (throat and bronchus), gastrointestinal tract (esophagus, large intestine and perianal, stomach, small intestine, and bile duct). Malignant GCT account for 1%-2% of this tumor. The number of reported diagnoses in the thoracic wall is less than 5, and almost all of them are benign. We report a new case of malignant granular cell tumor of the thoracic wall with rib invasion and pleural metastasis in a male Asian. Microscopically eosinophilic cytoplasmic, granular, and round cells without prominent atypia were presented but clinically rapidly progressed. One is histological morphology “benign” but clinically “malignant.”